1990
DOI: 10.3758/bf03203190
|View full text |Cite
|
Sign up to set email alerts
|

A novel automatic procedure for measuring ocular counterrolling: A computeranalytical method to determine the eye’s roll angle while subjects work on perceptual tasks

Abstract: In investigations ofthe perception ofspace, the consideration of ocular counterrolling-the movement of the eye around its visual axis in response to body movement-is crucially important. The angle ofthis movement must be known in order for one to determine the precise retinal coordinates of a distal object. Following transformation, this stimulus serves as a reliable cue for visual direction. The otolith organs provide information about body tilt and are responsible for ocular counterrolling. A novel, noninvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It was based on the algorithm described by Bucher, Heitger, Mast, and Bischof (1990). Circular profiles were recorded on the picture of the iris, around the center of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…It was based on the algorithm described by Bucher, Heitger, Mast, and Bischof (1990). Circular profiles were recorded on the picture of the iris, around the center of the pupil.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular torsional position: The onboard optical components in the centrifuge, the procedure and the algorithm to determine the OCR have been fully described elsewhere (Bucher, Heitger, Mast, & Bischof, 1990). Briefly, the subject's head was stabilized by a removable bite-board with individual dental impressions.…”
Section: Methodsmentioning
confidence: 99%
“…They observed that the preferred position for adjusting the SVV sometimes sticks out of the subject's frontal plane even though the body is tilted in roll only. A detailed description of the apparatus used in this study is given elsewhere (Bucher, Heitger, Mast, & Bischof, 1990). …”
Section: Apparatusmentioning
confidence: 99%